2013
DOI: 10.1159/000351129
|View full text |Cite
|
Sign up to set email alerts
|

Cell Projections and Extracellular Matrix Cross the Interstitial Interface within the Renal Stem/Progenitor Cell Niche: Accidental, Structural or Functional Cues?

Abstract: Background: During nephron induction, morphogenetic molecules are reciprocally exchanged between epithelial and mesenchymal stem/progenitor cells within the renal stem/progenitor cell niche. That these molecules remain concentrated, it is assumed that both cell populations stand in close contact to each other. However, recently published data illustrate that epithelial and mesenchymal cells are separated by an astonishingly wide interstitial interface. Methods: To gain deeper morphological insights into the sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 48 publications
1
22
1
Order By: Relevance
“…Animal studies have identified nanotubes or similar structures in vivo in an inflammatory corneal mouse model (Chinnery et al, 2008; Seyed-Razavi et al, 2013) and ex vivo in adult mouse heart tissue (He et al, 2011), mouse alveoli (Islam et al, 2012), rabbit kidney parenchyma (Minuth and Denk, 2012), and mouse embryo non-neural ectoderm (Pyrgaki et al, 2010). Our group was the first to image TnTs in resected human tumor samples, initially on tumors from patients with MPM and lung adenocarcinoma (Lou et al, 2012b); we have been able to reproduce this finding using human mesothelioma tumors described in the current study (Movie S5).…”
Section: Resultsmentioning
confidence: 99%
“…Animal studies have identified nanotubes or similar structures in vivo in an inflammatory corneal mouse model (Chinnery et al, 2008; Seyed-Razavi et al, 2013) and ex vivo in adult mouse heart tissue (He et al, 2011), mouse alveoli (Islam et al, 2012), rabbit kidney parenchyma (Minuth and Denk, 2012), and mouse embryo non-neural ectoderm (Pyrgaki et al, 2010). Our group was the first to image TnTs in resected human tumor samples, initially on tumors from patients with MPM and lung adenocarcinoma (Lou et al, 2012b); we have been able to reproduce this finding using human mesothelioma tumors described in the current study (Movie S5).…”
Section: Resultsmentioning
confidence: 99%
“…The epithelial stem cells contained here exhibit a simple cuboidal shape. In the optical microscope, one can see that the tip of a CD ampulla does not touch the neighboring mesenchymal stem cells, but is separated by a striking interface as was observed in neonatal rabbit kidney [53]. On sections oriented along the axis of lining CD tubules, one can also see that only 2 layers of mesenchymal stem cells occur between the tip of a CD ampulla and the inner side of capsule.…”
Section: View By Optical Microscopymentioning
confidence: 99%
“…For example, to date it is hardly perceived that during the late phase of parenchyma formation, induction of nephrons occurs in close vicinity, in a structured pattern and in a special microenvironment of extracellular matrix on the inner side of the organ capsule (Table 1; Fig. 2, 3) [53, 57, 58]. Besides an intact morphogenetic activity, the site, amount, and arrangement of competent cells within niches must also be carefully analyzed when causes of impaired nephrogenesis in preterm and low birth weight babies are under debate [20, 23].…”
Section: Call For Future Investigationsmentioning
confidence: 99%
“…Driven by the mentioned temporal-spatial program and by permanent interactions between epithelial and mesenchymal stem/progenitor cells the parenchyma develops from the inner towards the outer cortex [23]. Until the neonatal period the stem/progenitor cell niche is not distributed at random but keeps an always close contact to the inner side of the organ capsule [24,25].…”
Section: Introductionmentioning
confidence: 99%